2009
DOI: 10.1007/s00586-009-1145-z
|View full text |Cite
|
Sign up to set email alerts
|

Association between osteoprotegerin gene polymorphism and bone mineral density in patients with adolescent idiopathic scoliosis

Abstract: Generalized low bone mass and osteopenia have been reported in the axial and peripheral skeleton of adolescent idiopathic scoliosis (AIS) patients. Recently, many studies have shown that gene polymorphisms are related to osteoporosis. However, no studies have linked the association between gene polymorphisms and bone mass of AIS. Therefore, this study examined the association between the bone mass and RANKL, RANK, and OPG gene polymorphisms in 198 girls diagnosed with AIS. OPG 163 A --> G, 209 G --> A, 245 T -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 33 publications
1
23
0
3
Order By: Relevance
“…This data corroborates evidences in which G1181C polymorphism as well as CC genotype was associated to normal BMD in Korean patients with Adolescent Idiopathic Scoliosis [34]. A previous study demonstrated G allele and GG genotype carried out a bone mineral density 3.7% lower in women than women with CC genotype [35].…”
Section: Discussionsupporting
confidence: 79%
“…This data corroborates evidences in which G1181C polymorphism as well as CC genotype was associated to normal BMD in Korean patients with Adolescent Idiopathic Scoliosis [34]. A previous study demonstrated G allele and GG genotype carried out a bone mineral density 3.7% lower in women than women with CC genotype [35].…”
Section: Discussionsupporting
confidence: 79%
“…Adolescent idiopathic scoliosis patients have been reported to have a low bone mass and osteopenia in both the axial and peripheral skeletons [6,8,11,13,35,38]. However, the precise mechanism of bone loss in AIS patients is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Generalized low bone mass and osteopenia in both the axial and peripheral skeletons have been reported in AIS [7,8,11,13,35,38], and abnormal histomorphometric bone cell activity has been observed in AIS bone biopsies [9]. In addition, low bone mass is likely to persist through to adulthood in AIS patients [7], and there is increasing concern that adolescents with idiopathic scoliosis might have a lower peak bone mass, which would increase the risk of developing osteoporosis and related complications in later life [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that central to the regulation of bone mass is osteoblast expression of receptor activator of nuclear factor kappa-B ligand (RANKL), which stimulates osteoclast activity and bone resorption by binding to RANK on the osteoclast membrane, and the osteoblast expression of osteoprotegerin (OPG), which acts as a decoy receptor for RANKL, thus inhibiting osteoclast activity and bone resorption [30]. Critically, genetic studies have shown associations between LSBMD with polymorphisms of OPG in girls diagnosed with AIS [16]. Furthermore, increased serum concentration of RANKL and an increase in the RANKL:OPG ratio, which would promote greater bone resorption, have been reported in patients with AIS, and were found to be negatively correlated to LSBMD [55].…”
Section: Intrinsic Factors Of the Ais Spinal Musculoskeletal System Smentioning
confidence: 99%